Castroism and communism in Latin America, 1959-1976 : the varieties of Marxist-Leninist experience - Ratliff, William E. (Washington : American Enterprise Institute for Public Policy Reearch, 1976)
This study is devoted primarily to the strategy tactics, and activities of communist and castroite parties and organizations seeking power or influence in Latin America during the period from 1959 to 1976, emphasizing the years of greatest diversity between 1964 and 1973.
Includes bibliographical references and index.
osa 22/01/19
Loans
Keywords: Communism; Cuba; Latin Ameriac